THE ROLE OF LEARNING MANAGEMENT IN THE PANDEMIC TIME COVID-19 TOWARDS THE LEARNING ACHIEVEMENT OF CLASS II STUDENTS OF SDN INPRES 2 TANAMODINDI - Nur Hasifa; Rizal Rizal; Sisriawan Lapasere (Universitas Tadulako, 2021)
The problem in this research is that the focus of the teacher is only on providing material by taking notes and reading the subject matter, the teacher's teaching strategy is still not optimal in improving learning outcomes, especially during the Covid-19 pandemic. The teacher as the main component in the school in the teaching and learning process can manage the learning process with a good teaching strategy as a motivator in improving student learning achievement. The purpose of this research was to determine the relationship between the role of teacher learning management and the learning achievement of grade II students of SD Inpres 2 Tanamodindi. This type of research is a qualitative description. The subjects taken in this study were 18 and 11 teachers. Application of learning management which includes functions; planning, organizing, mobilizing, and controlling, indicated by a mean score of 80.08: 23 = 3.48 with the frequent category. Thus, the teachers at SD Inpres 2 Tanamodindi often apply the role of learning management in carrying out the learning process and the learning achievement of students in Civics, BI, MTK and Social Studies subjects at SD Inpres 2 Tanamodindi is 75.94 with a high category.